Central bank digital currencies as an element of the payment-centric model of global financial regulation - V. E. Ponamorenko; G. A. Nasyrova; E. S. Molotova (Цифровое право, 2023)
The article examines the current state of implementation of one of the largest regulatory projects in to examine the role of international cross-border payment regulation in the context of global financial architecture and to see how a modernized national payment infrastructure could be optimally embedded in the global payment infrastructure. To achieve this purpose, this article systematizes the standard setting documents and analyzes doctrinal sources. Special attention is paid to BIS Innovation Hub projects. The study analyses area E of the G20 Roadmap, which covers the development of new means of payment, including CBDCs and stablecoins. In particular, the paper provides an overview of analytics and specific projects pertaining to the introduction of central bank digital currencies (CBDC). The article also analyzes how the issuance of CBDCs relates to the international framework being created for regulating crypto assets. The authors conclude that global financial regulation is becoming more payment-centric since the issue of regulating cross-border payments lies at the intersection of several important policies and international legal regimes. In particular, this involves international policies pertaining to the regulation of financial services, macroprudential regulation, regulation of the global monetary system, regulation of crypto assets, countering illicit financial flows in the global economy, and ESG regulation. The article systematizes the features and risks of the payment-centric model for global financial regulation. It concludes that international cooperation and coordination are necessary if cross-border projects related to payments are to be successfully implemented.